CONTROLLING FACTOR IN ALUMINA PILLARED SAPONITE AND ALUMINA PILLARED MONTMORILLONITE SYNTHESIS - Is Fatimah; Narsito Narsito; Karna Wijaya (Universitas Gadjah Mada, 2009)
The effect of synthesis parameters to the physical properties of pillared saponite and pillared montmorillonite was examined. Mol ratio of Al to clay mass in the range 1.0 - 5.0 and two different calcination methods; conventional calcination and microwave irradiation method are evaluated as controlling factors to evolution of basal spacing d001 , surface acidity, specific surface area, pore distribution and catalytic activity in phenol hydroxylation reaction. XRD, FTIR, and N2-adsorption/desorption analysis were used to characterize the materials. Results showed that pillarization produced higher basal spacing d001 and surface acidity and crystalinity of materials in all Al/clay ratio and in both of the calcination methods. In general, Al to clay mass ratio and calcination method remarkably influence to the basal spacing d001, surface acidity and material crystallinity, but the effect of these factors to catalyst activity in phenol hydroxylation depends on nature of clay. It is concluded that the activity as catalyst is affected by the presence of ionic species and surface acidity in the minerals.